"I've seen my friend get chopped": The Influence of Peer Networks on Exposure to Violence Among Homeless Young Adults. Issue 3 (May 2021) - Heerde, Jessica A.; Pallotta-Chiarolli, Maria
Homeless young adults report being exposed to substantial violence and victimization. This often arises through street culture and norms associated with subcultures of violent behavior. In this exploratory study, we applied a decolonizing lens to conduct semi-structured interviews with 18 young adults experiencing homelessness in Victoria, Australia. In this study, we provide a contemporary description of peer relationships among homeless young adults. We examine how these relationships influence exposure to violence, and how young adults perceive and respond to injuries sustained by their peers because of exposure to violence. Findings showed bonds and relationships between homeless young adults appear to imitate the rapport and functions of sibling-kinship that typically exist in supportive family environments. Despite the care and protection provided within close peer relationships, these relationships may also contribute to exposure to violence by way of young adults witnessing violence perpetration and incidences of peers being physically victimized. There is an important duality between the perceived normalization of witnessing peers' experiences of violence and young adults' self-reflexive disclosure of vulnerability and helplessness in witnessing these incidents. Study findings have important research and practice implications for recognizing the influence and importance of peer relationships in the delivery of homelessness support programs.